The inhibitory effect of glucagon-like peptide-1 (GLP-1) 7-36 amide on gastric acid secretion in humans depends on an intact vagal innervation. - Wettergren, A (Gut, 1997)
BACKGROUND: Glucagon-like peptide-1 (GLP-1)(7-36) amide is an intestinal incretin hormone which also inhibits gastric acid secretion in humans. Its mechanism of action is unclear, but it strongly inhibits vagally induced secretion (sham feeding), suggesting that it could influence vagal activity. AIM/METHODS: The effect of intravenous GLP-1 (7-36 amide) (1 pmol/kg/min) was studied on pentagastrin induced acid secretion in otherwise healthy subjects, previously vagotomised for duodenal ulcer (n = 8) and in a group of young (n = 8) and old (n = 6) healthy volunteers. RESULTS: Pentagastrin increased acid secretion significantly in all three groups, but the plateau concentration in the vagotomised subjects was lower than in controls. Infusion of GLP-1 (7-36 amide) significantly inhibited acid secretion in the control groups (to 67 (SEM 6) and 74 (SEM 3)% of plateau concentrations in young and old controls, respectively) but had no effect in the vagotomised subjects. Differences in plasma concentrations of GLP-1 (7-36 amide), recovery of gastric marker, duodenal regurgitation, or Helicobacter pylori status could not explain the lack of effect. Blood glucose was lowered equally by GLP-1 (7-36 amide) in all subjects. CONCLUSION: The inhibitory effect of GLP-1 (7-36 amide) on acid secretion depends on intact vagal innervation of the stomach.